2014
DOI: 10.1002/cam4.164
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of preoperative capecitabine in women with operable hormone receptor positive breast cancer

Abstract: Conventional preoperative chemotherapy regimens have only limited efficacy in hormone receptor positive (HR+) breast cancer and new approaches are needed. We hypothesized that capecitabine, which is effective in metastatic breast cancer, may be an active preoperative treatment for HR+ breast cancer. Women with HR+, HER2-negative operable breast cancer received capecitabine, 2000 mg/m2 daily in divided doses for 14 days, followed by a 7-day rest period. Treatment was repeated every 21 days for a total of four c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Meanwhile, TSTA3 was shown to participate in the biosynthesis of GDP-L-fucose, and the expression level of TSTA3 was correlated with poor prognosis for patients with esophageal squamous cell carcinoma (44). TYMP has been reported to be associated with the conversion of capecitabine to 5-FU (45). Previous study has also indicated that the expression level of TYMP was associated with capecitabine response (46).…”
Section: Discussionmentioning
confidence: 96%
“…Meanwhile, TSTA3 was shown to participate in the biosynthesis of GDP-L-fucose, and the expression level of TSTA3 was correlated with poor prognosis for patients with esophageal squamous cell carcinoma (44). TYMP has been reported to be associated with the conversion of capecitabine to 5-FU (45). Previous study has also indicated that the expression level of TYMP was associated with capecitabine response (46).…”
Section: Discussionmentioning
confidence: 96%
“…Arowolo et al reported that capecitabine monotherapy achieved good overall response rates with manageable toxicity when administered as neoadjuvant chemotherapy to 16 patients with locally advanced breast cancer (16). In a phase II study by Tolaney et al, 3 patients exhibited a complete clinical response after 4 cycles of capecitabine monotherapy and 8 patients exhibited a partial clinical response among 24 women with operable hormone receptor-positive breast cancer (17). Li et al reviewed the randomized controlled trials that included capecitabine in the neoadjuvant chemotherapy for breast cancer and concluded that adding capecitabine to neoadjuvant chemotherapy was unlikely to improve the outcomes in breast cancer patients without distant metastases (18).…”
Section: Discussionmentioning
confidence: 99%